2017
DOI: 10.5897/ajar2017.12384
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deprivation of selected single nutrients on biometric parameters of cedar seedlings (Acrocarpus fraxinifolius) grown in nutritive solution

Abstract: The purpose of this work was to assess biometric parameters of cedar seedlings (Acrocarpus fraxinifolius) associated with visual symptomatology of macronutrients deficiency, growth rate, and content and accumulation of nutrients in aerial parts of seedlings grown in nutritive solution. The trial was established in completely randomized design with seven treatments, four replications, and one plant per pot. Treatments consisted of complete nutrient solution, Hoagland and Arnon, and deprivation of the following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…Furthermore, the omission of Ca inhibited the development of the roots of the ipê seedlings, which exhibited an aspect of necrosis (Figure 2c), as reported by Munguambe et al, (2017) in cedar seedlings.…”
Section: Calcium Omissionsupporting
confidence: 63%
See 3 more Smart Citations
“…Furthermore, the omission of Ca inhibited the development of the roots of the ipê seedlings, which exhibited an aspect of necrosis (Figure 2c), as reported by Munguambe et al, (2017) in cedar seedlings.…”
Section: Calcium Omissionsupporting
confidence: 63%
“…The seedlings of ipe cultivated under omission of N expressed as symptomatology the generalized chlorosis (Figure 1b), which started in the leaves closest to the base (mature leaves) and gradually evolved to the apical leaves (juvenile leaves), affecting all the leaves, as described by (Malavolta, 2006). Similar symptoms were observed in Brazilwood seedlings (Valeri et al, 2014), african mahogany -Khaya ivorensis e K. anthotheca (Viera et al, 2015;Corcioli et al, 2016) and cedar (Munguambe et al, 2017). Such symptomatology manifested in the leaves, according to Viégas et al, (2014), occurs due to the collapse of chloroplasts as a function of proteolysis, resulting in the degradation of chlorophyll molecules which promotes the yellowing of the leaves.…”
Section: Nitrogen Omissionsupporting
confidence: 53%
See 2 more Smart Citations
“…The optimal N, P and K contents for A. fraxinifolius are 23.28, 1.98 and 5.15 g Kg -1 , respectively, and the contents of plants in deficiency are 11.3, 1.3 and 2.17 g Kg -1 , respectively (Munguambe et al, 2017). The study showed that the main limiting factor for growth was nitrogen, since only treatments 7 and 8 reached adequate levels, while all the treatments with slow release fertilization and the treatment with half of the fractional fertilization (T6) obtained intermediate values between deficient and adequate.…”
Section: Resultsmentioning
confidence: 97%